The Victory bombers the B-24 - Katz, Frank J. ([Los Angeles, Calif.] Prime Cut Productions, 2007)
"During World War II, Nazi Germy and Imperial Japan divided and conquered much of the globe. When the U.S. entered the war, the battered Allies unleashed massive air power to turn back the Axis assault. This is the story of the brave men who flew the lethal bombers that spewed terror fromthe skies and were crucial in devastating the enemy war machine. Their heroic saga of raw courage and mechanical genius will thrill generations to come." --container.
Disc 1. Target Nazi Europe -- Disc 2. Bombers over Normandy -- Disc 3. Target Japan.
Director, Frank Katz; producer, Janice Kaplan; written by Edward Flaherty.
DVD videos.
Keywords: World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- France -- Normandy; World War, 1939-1945 -- Japan; World War, 1939-1945 -- Europe; B-24 (Bomber); Documentary films